Ricardo Caballero - Artificial Neural Networks In The Prediction of Atheroma Plaque Vulnerability - Caballero, Ricardo (Jornada de Jóvenes Investigadores del I3A, 2022)
Artificial Neural Networks In The Prediction Of Atheroma Plaque Vulnerability